Professional burnout and patient safety culture in Primary Health Care - Vitória Talya dos Santos Sousa; Hirlana Girão Dias; Fernanda Pereira de Sousa; Roberta Meneses Oliveira; Edmara Chaves Costa; Patrícia Freire de Vasconcelos (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the association between the risk of occupational exhaustion (burnout) and safety culture in Primary Health Care. Methods: ross-sectional study conducted in 18 Primary Health Care Units in the Northeast of Brazil. Three questionnaires were used: sociodemographic, Maslach Burnout Inventory, and the Medical Office Survey on Patient Safety Culture. The study was approved by the Research Ethics Committee. Results: seventy-eight healthcare workers participated, of which 64.1% presented a reduced risk of burnout; and 11.5%, a high risk (p=0.000). The following were identified as weakened dimensions of safety culture: Work pressure and pace; Owner, managing partners, leadership support; Overall ratings on quality; and Overall rating on patient safety. Conclusions: an association was found between low risk of developing burnout syndrome and positive evaluation of safety culture.